Association effects of glyphosate and phosphite in maize plants - Gomes, Giovanna Larissa Gimenes Cotrick [UNESP]; Velini, Edivaldo Domingues [UNESP]; Carbonari, Caio Antonio [UNESP]; Trindade, Maria Lucia Bueno (Revista Brasileira de Herbicidas, 2013)
The objective of this study was to evaluate the effects of glyphosate herbicide association with potassium phosphite in maize plants. The experiment was accomplished in green house conditions, with seeding of Pioneer 30F53H simple hybrid in vases. Experimental design used was entirely randomized with six treatments and four replications. Treatments application was made with plants in V7 developmental stage. Evaluations of electron transport rate (ETR) in photo system II were conducted during periods of 1, 2, 5, 32, 56, 80, 104, 128, 152, 176, 200 and 360 hours after application (HAA), as well as visual determinations of intoxication in the same plants at 2, 4, 6, 10 and 15 days after application (DAA). At the end of experiment (15 DAA) it was determined plants height with a graduated ruler from soil level as far as the insertion of last leaf fully expanded, and leaves and stalks dry mass. Glyphosate association with potassium phosphite Fosway® (3.0 L ha-1 , with 30% of P2O5 and 20% of K2O) with 72 g a.e. ha-1 dose increased the levels of plant intoxication. Maize plants submitted to 72 g a.e. ha-1 dose alone showed higher growth than control. ETR of treated plants showed an increase in the first hours after application, and subsequent reduction in plants exposed to higher doses of glyphosate associated or not with potassium phosphite.

O objetivo deste estudo foi avaliar os efeitos da associação do herbicida glyphosate com fosfito de potássio em plantas de milho. O experimento foi conduzido em casa-de-vegetação, com a semeadura do híbrido simples Pioneer 30F53H em vasos. O delineamento experimental utilizado foi inteiramente casualizado com seis tratamentos e quarto repetições. A aplicação dos tratamentos foi realizada com as plantas em estágio V7. Foram realizadas avaliações da taxa de transporte de elétrons (TTE) no fotossistema II nos períodos de 1, 2, 5, 32, 56, 80, 104, 128, 152, 176, 200 e 360 horas após a aplicação (HAA) e também se efetuou determinações visuais de intoxicação das mesmas plantas aos 2, 4, 6, 10 e 15 dias após a aplicação (DAA). No final do experimento (15 DAA) determinou-se a altura das plantas com régua graduada rente ao solo até a inserção da última folha totalmente expandida, e a massa seca de folhas e colmos. A associação do fosfito de potássio Fosway® (3,0 L ha-1 , com 30% de P2O5 e 20% de K2O) com o glyphosate na dose de 72 g e.a. ha-1 aumentou os níveis de intoxicação das plantas. As plantas de milho submetidas à dose de 72 g e.a. ha-1 isolada, apresentaram maior crescimento do que as da testemunha. O TTE das plantas tratadas apresentou incremento nas primeiras horas após a aplicação, e posterior redução nas plantas submetidas a 720 g e.a. ha-1 de glyphosate associada ou não ao fosfito de potássio.
Efeitos da associação de glyphosate e fosfito em plantas de milho
Keywords: Electron transport rate; Phytotoxicity; Zea mays L.; Taxa de transporte de elétrons; Fitotoxicidade; Zea mays L.